Juridical Analysis of the Etawaku Trademark Cancellation in Business Cooperation - Tsani, Sulthan Mada Maulana; Indrawati, Septi (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
Brand is an important component in a business. Trademarks have the power to shape a company's image and influence consumer decisions. Nevertheless, there are registered trademarks with similarities or similarities with previously registered trademarks and the first registrant feels disadvantaged, so that legal efforts can be made to cancel the trademark, remove the trademark, or apply for compensation. This study aims to determine how the consequences of cancellation of the trademark against business cooperation agreements, to achieve these objectives can be done through the method of normative legal research with more emphasis on understanding in obtaining answers by basing on the principles and principles of law applied to regulate the sovereignty of a country. The results show that the cancellation of the